Cytotoxicity Effect of Laserpitium Carduchorum Extract in Mcf-7 Human Breast Cancer Cells Via Cell Cycle Arrest and Induction if Apoptosis - Ahmed Mustafa, Twana; Ismael Mohammed, Hero (International Journal of Psychosocial Rehabilitation, 2020)
Laserpitium carduchorum is a perennial herb belonging to the Apiaceae family. In Iran, this plant is found in the Kurdistan Province, Bane Mountains. Several species of genus Laserpitium showed antibacterial, anti-fungal, cytotoxic, anti-tumor and anti-inflammatory activities. In this study, we investigated the effect of L. carduchorum methanolic extract on the MCF-7 and HEK293 cell lines by MTT assay, induction of apoptosis, cell cycle arrest, and expression of some apoptotic genes. After treatment of cells with plant extract, the plant was significantly (P < 0.0001) cytotoxic to MCF-7 and cytotoxic to HEK293 at high-dose treatment (1000 μg/ml). IC50 for each cell evaluated. Proper IC50 for MCF-7 was 55.25μg/ml and 725.9μg/ml for HEK293. Cell cycle arrest and apoptosis were analyzed by using a FACSCanto II (BD Biosciences flow cytometry, cells arrested at S and G2/M phase(P<0.01, P<0.05)L. Carduchorum induced a marked increase (P < 0.001) in the percentage of early and late apoptotic. Real-time PCR was performed to analyze the expression of some apoptotic genes (Bax, Bcl-2, Caspase 3 and Caspase 9)Bax, a central cell death regulator, is an indispensable gateway to mitochondrial dysfunction and a major pro-apoptotic member of the B-cell lymphoma 2 was expressed significantly (p <0.05) after cells treatment of cell.